In Vitro Selection of Peanut Somatic Embryos on Medium Containing Culture Filtrate of Sclerotium rolfsii and Plantlet Regeneration - YUSNITA YUSNITA; WIDODO WIDODO; SUDARSONO SUDARSONO (HAYATI Journal of Biosciences, 2005)
Attempts to identify somaclonal variants of peanut with resistance to Sclerotium stem rot disease due to infection of S. rolfsii were conducted. The objectives of this study were to develop in vitro selection method using culture filtrates of S. rolfsii, identify culture filtrate-insensitive somatic embryo (SE) of peanut after in vitro selection and regenerate peanut R0 lines originated from culture filtrate-insensitive SE. To achieve these objectives, peanut embryogenic tissues were cultured on selective medium containing various concentrations of S. rolfsii culture filtrates and sublethal concentration of the filtrates. Medium containing sublethal level of S. rolfsii culture filtrates was used to identify culture filtrate-insensitive SE of peanut. Subsequently, the selected SEs were germinated, plantlets were regenerated and preliminary tested against S. rolfsii. Results of the experiments showed that addition of S. rolfsii culture filtrates into medium for inducing peanut somatic embryos drastically reduced their growth and proliferation. S. rolfsii culture filtrates at 10% concentration has significantly reduced the number of proliferated SE per explant. However, sublethal level was achieved at 30% of culture filtrates concentration. Responses of five peanut cultivars against 30% of culture filtrates were similar, indicating they were similar in their susceptibility against S. rolfsii. A number of culture filtrate-insensitive SE were identified after culturing 1500 clumps of embryogenic tissue of peanut cv. Kelinci for three consecutive passages on medium containing 30% of culture filtrates. Germination of selected SE and regeneration of plantlet from culture filtrate-insensitive SE resulted in 50 peanut R0 lines. These lines have been grown in the plastic house and produced normal seeds for further evaluation. Results of S. rolfsii inoculation indicated the existence of chimera for insensitivity against S. rolfsii.